An Analytical Dataset of Approaches to V in Mozart - Brown, Jenine; Tan, Daphne; Lin, Michelle (Empirical Musicology Review, 2023)
Tonal functions—tonic, pre-dominant, and dominant—are a standard feature of North American music theory. The pre-dominant (PD) encompasses the largest number of chords, varying in quality and scale degrees; unlike the tonic and dominant functions, it is primarily defined by its syntactical role, preceding the arrival of the dominant. While Western harmony textbooks consistently organize PD chords according to a regulative syntax (e.g., IV goes to ii), they differ on its rationale and are rarely explicit about the repertoire(s) on which it is based. Furthermore, while the PD is thought to be an essential element of cadential closure, the role of PDs at various formal locations is underexplored, be it in textbooks or corpus studies. To facilitate exploration of these claims for future research, we analyzed all 22 sonata-allegro movements from the Mozart piano sonatas and generated a new dataset containing every occurrence of V (including the Cad6/4), the three chords preceding each V, and their formal location.